Adsorption of phosphate by paper mill sludge / Ahmad Razali bin Ishak - Ahmad Razali, Ishak (2011)
The utilization of paper mill sludge as adsorbent for removal of phosphates from aqueous solution has been investigated. The influences of experimental condition such as pH of solution, amount of adsorbent and initial concentration of phosphate were studied in detail. The adsorption of phosphate was pH dependant and adsorption process being more efficient in the basic pH region and maximum at pH 12. The adsorption isotherm and adsorption kinetics of paper mill sludge were studied. It shows that the Langmuir model is better in describing the adsorption isotherm process compared to Freundlich. The maximum adsorption capacity was 12.65 mg/g at pH 12 at room temperature. Two kinetics models, pseudo-first order and pseudo-second order were applied in order to analyze the kinetics data. It was found that the pseudo-second order model is the better choice to describe the adsorption behavior. The thermodynamics parameters have been evaluated. Thermodynamic calculations showed that the phosphate adsorption process of paper mill sludge was endothermic and spontaneous in nature. From the study, the paper mill sludge has the potential to be utilized as cost effective removal of phosphate from real water samples due to their low cost and high capability.